The influence of job satisfaction towards turnover intention among nurses in Yan Hospital / Nik Muhammad Zulhamiz Zulkifli and Nurhanis Abd Hamid - Zulkifli, Nik Muhammad Zulhamiz; Abd Hamid, Nurhanis (2019)
Globally, a shortage of qualified nurses, higher turnover rates and low retention are ongoing issue for health organizations around the world (Buchan & Aiken, 2008). Bobbio and Manganelli (2015), concluded that nurse retention could be regarded as one of the world’s leading healthcare organization challenges. This high turnover has increased the number of shortage nurses (De Gieter, Hofmans, & Pepermans, 2011). The nursing profession continues to face shortages due to lack of potential educators, high turnover and inequitable distribution of the workforce (Sawaengdee, et al., 2016).